IGREJA SEM FRONTEIRAS, FRONTEIRAS SEM IGREJA: Análise das Práticas Pastorais nas Igrejas Batistas da Região Leste da Cidade de São Paulo, num Contexto Urbano de Contrastes, de 1990 a 2000, na Perspectiva da Teologia Prática - Dias, Jorge Schütz (2004)
Cities develop around nucleuses called centers in the direction of circular peripheries. The populations that live and establish relationships in these frontier zones establish specific relationships with the space that they occupy and with the nucleus called the center. In São Paulo it is plausible that there does not exist uniformity in the urban population, but urban populations marked by pluralism and significant contrasts, including manifestations of religious phenomenon. The east zone of the city of São Paulo is the object of analysis of this research presented in four chapters. What is observed in this region are a variety of different aspects within the geographic region identified as ZL, including, more specifically, ZL1 and ZL 2, which demonstrate the contrasts that exist in this frontier region. The specific perspective on this space is delimited by time, between 1990 and 2000, and by the research reference that proposes to identify and analyze Pastoral Practices of Baptist Churches in this Zone. In the analysis of Pastoral Practices in terms of evangelization and missionary expansion, the research is specifically elaborated around three communities: The First Baptist Church of Penha, the Baptist Church in Vila Salete and the First Evangelical Baptist Church in Guaianases. The research is accomplished not by a referential external to the communities, but from the respective proposals of Pastoral Practices registered in official documents such as minutes, yearly reports and information from Sunday bulletins that serve as documental sources. Urban frontiers are, by nature, innovative and chaotic, and this is exactly the space for the creation and development of Pastoral Practices in churches within this context. In this sense, these churches are not limited in terms of innovation, and may be understood as Churches without Borders. Without such flexibility these churches would not be able to enter into dialog with this urban frontier, and would be excluded from the environment of contrasts in such a way that would generate the vacuum, despair, of a Frontier without a Church.(AU)